Pharmacoeconomic analysis of drug expenditure in government medical college and hospital, Vijayawada, India - Reddy, Y. Bala Suresh Kumar; K., Sankar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: To conduct economic analysis in tertiary care hospital with a view to identify the categories of drugs needing stringent management control. Methods: The annual consumption and expenditure data is obtained from the drug store of government general hospital, Vijayawada, for the period of April 2015 to March 2016. ABC-VED analysis of the drugs are done based on cost and criticality criteria respectively. ABC-VED matrix analysis was done to classify drugs into category I, II, III. Results: The total annual drug expenditure incurred on 299 drug items for the year 2015-2016 was found to be Rs:4,47,04,446. On ABC analysis, 4%, 9.36%, 86.64% of drugs were found to be Always, Better, and Control category items respectively, amounting to 68.92%, 20.05%, 11.03% of annual drug expenditure. VED analysis showed that 32.10%, 45.5%, 22.4% of drug items were Vital, Essential, and Desirable category items respectively, amounting to 35.3%, 37.1%, 27.6% of annual drug expenditure respectively. By ABC-VED matrix analysis, 34.11%, 46.49%, 19.4% of drug items were found to be category I (high stringent), II (medium stringent), III (low stringent) respectively, amounting to 80.76%, 17.46%, 1.77% of annual drug expenditure respectively. Conclusions: The study identified 34.11% of drug items belonging to category I which require high priority monitoring. Inventory management tools must be routinely used for the better control and judicious use of the resources.